Correlation between Subclinical Heart Disease and Cardiovascular Risk Profiles in an Urban Emergency Department Population with Elevated Blood Pressures: A Pilot Study - Prendergast, Heather M. (J Emerg Med, 2015)
OBJECTIVE: Determine the point prevalence of left ventricular hypertrophy and diastolic dysfunction in an urban emergency department (ED) population with elevated blood pressures (EBP) and examine the correlation between subclinical disease and patient cardiovascular risk profiles. METHODS: A convenience sample of emergency department patients with elevated blood pressures (blood pressure ≥ 140/90 mm Hg on at least 2 measurements) with or without a history of hypertension were enrolled. Subjects had limited bedside echocardiograms performed by ED physicians with ultrasound training and baseline laboratory studies obtained. Patients were classified as having subclinical hypertensive heart disease if any of the following were identified using standard echocardiogram criterion: left ventricular hypertrophy, abnormal ejection fraction, or diastolic dysfunction. RESULTS: A total of 39 patients with EBP were enrolled. The mean age was 46 years (SD 10.9 years), 59 % (n=23) were women, 21% (n=8) were smokers, and 92% had a history of hypertension (n=33). The average BMI was 30.7 (SD=8.7). Racial/ethnicity included African Americans 67% (n=26), Latinos 23% (n=9), Caucasian 5% (n=2), Asian and Native Americans 3% (n=1 respectively). Subclinical hypertensive disease was found in 39% (n=15) with 31% (n=12) having left ventricular hypertrophy, 15% (n=6) having evidence of diastolic dysfunction and 8% (n=3) having abnormal ejection fraction. On bivariate analysis elevated diastolic blood pressure (p=0.039) and blood urea nitrogen (p=0.016) were correlated with the presence of subclinical heart disease. After adjusting for other covariates, receiving oral/intravenous antihypertensive medications in the ED (p= 0.005) was associated with subclinical heart disease in multivariate regression analysis. CONCLUSIONS: We found a point prevalence of subclinical heart disease of 39% in this urban ED population with EBP screened using limited bedside echocardiograms performed by ED physicians. Identification of subclinical heart disease at early stages in real-time in the ED in conjunction with abnormal renal function can help ED physicians risk stratify and identify those patients in need of more aggressive therapy and urgent follow-up thus decreasing the likelihood of cardiovascular disease progression and complications such as heart failure and renal failure at later stages.